U.S. Army Air Forces special air navigation chart : Newfoundland to Northwest Africa - United States. Army Map Service (Washington (D.C.), 1943)
Colour. "Advance edition, subject to correction" (top edge). Six compass roses with variation based on location. Relief shown by hachures and spot heights. 250-mile bar scales along side edges. Includes notes. Map shows basic features plus special information for pilots, with legend.